Integrating Omics Technologies in Microbial Research - Nazia Khan, (The Bioscan, 2024)
Omics technologies, encompassing genomics, transcriptomics, proteomics, and metabolomics, have significantly advanced the study of microbial systems. This paper examines how the integration of these diverse approaches can provide a comprehensive understanding of microbial functions, interactions, and their roles in various environments. We explore recent developments in sequencing technologies and computational tools that enable detailed analysis of microbial communities and their metabolic activities. The paper includes case studies demonstrating the application of integrated omics to investigate microbial responses to environmental factors, uncover mechanisms of disease, and discover new bioactive compounds. Additionally, we address the challenges of data integration and the importance of developing standardized protocols. Integrating omics technologies has the potential to enhance our knowledge of microbial diversity and functionality, offering valuable insights for applications in biotechnology, medicine, and environmental science